Corticoid-induced myopathy in a patient with Sjögren's Syndrome: Case report and literature review (Research, Society and Development, 2024)
Glucocorticoid-induced myopathy is a toxic disease caused by the exogenous administration of these drugs, either orally or intravenously. Clinically, it is characterized by weakness and low endurance of the skeletal muscles. The aim of this article is to inform readers about how the prolonged use of corticosteroids can lead to the onset of myopathy, identifying how this affects the patient's quality of life. The present study reports the case of a patient diagnosed with Sjögren's Syndrome who presented complications of her pathology, necessitating the use of corticosteroids. Following the administration of the medication, the patient developed muscle weakness in the lower limbs. Based on the association between the clinical presentation, laboratory tests, and electroneuromyography, the main diagnostic hypothesis for the reported patient was corticosteroid-induced myopathy.